Pelatihan Pembuatan Bahan Ajar Berbasis Digital dalam Mendukung Implementasi Kurikulum Merdeka Belajar - Taufik, Taufik; Imansyah, M Nur; Rayhan, Moh; Jainab, Umul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The community service program at SMP Negeri 2 Woja implemented by a team of lecturers from STKIP Yapis Dompu aims to improve teachers' skills and knowledge in creating digital-based teaching modules, as well as support the implementation of the Independent Curriculum which requires teachers to be more adaptive and creative in using technology in the learning process. The emergence of challenges in utilizing digital technology and the lack of in-depth training for teachers prompted the implementation of this program, which consists of a series of training and mentoring. The training includes in-depth material on the principles of the Independent Curriculum and how to integrate technology in creating teaching materials, with participants trained to use digital platforms such as Canva to create more interactive and engaging teaching modules. The teaching methods used include lectures, group discussions, and hands-on practice in creating digital-based teaching modules. The results of the training showed a significant increase in teachers' knowledge and skills, with 90% reporting a better understanding of the Independent Curriculum and increased confidence in using digital platforms. In addition, the number of digital-based teaching modules produced increased from five modules to eighteen modules after the training, demonstrating the effectiveness of the program in developing teachers' practical skills. This program has contributed positively to the quality of learning at SMP Negeri 2 Woja, and the increase in teachers' understanding of the Independent Curriculum and their ability to utilize digital technology shows that this training intervention is much needed. In addition, this program opens up opportunities for further collaboration between SMP Negeri 2 Woja and STKIP Yapis Dompu in improving the quality of education in a sustainable manner, where the active involvement of teachers in creating digital-based teaching modules can have a significant impact on students' learning experiences in the future.